A bistable piezoelectric oscillator with an elastic magnifier for energy harvesting enhancement. (February 2017) - Wang, Guang-Qing; Liao, Wei-Hsin
Bistable oscillator has been recognized as an effective means by which to improve the linear resonant energy harvesting performance for its unique double-well restoring force potential. As oscillating in a high-energy orbit, the oscillator should be located at a distance from one stable to the other with a much higher velocity or acceleration. However, the vibration level in environment would be too low to provide the oscillator with a larger velocity to overcome the potential well barrier. This article is focused on the enhancement of a bistable piezoelectric oscillator with an elastic magnifier for high-energy orbit harvesting. The elastic magnifier positioned between the bistable piezoelectric oscillator and the base is to amplify the base vibration level in order to provide the bistable piezoelectric harvester with large movement. A 2-degree-of-freedom nonlinear lumped-parameter model of the bistable piezoelectric harvester with an elastic magnifier (bistable piezoelectric harvester + elastic magnifier) is derived to exhibit the large-amplitude periodic oscillation behaviors. With the comparison of the electromechanical responses obtained from theory and experiment, the results show that the output displacement, tip velocity, and harvesting voltage under open-circuit condition of the bistable piezoelectric harvester + elastic magnifier configuration are 15 mm, 1500 mm s −1, and 13 V, respectively, while those of the only bistable piezoelectric harvester configuration are 1 mm, 120 mm s −1, and 2 V under the excitation level of 8.69 m s −2 and frequency of 16 Hz. It is verified that the bistable piezoelectric harvester with an elastic magnifier can generate larger output performance than that of the bistable piezoelectric harvester without elastic magnifier at several excitation frequencies and levels.